Intraoperative monitoring parameters and postoperative delirium: Results of a prospective cross-sectional trial. Issue 1 (8th January 2021) - Jung, Carolin; Hinken, Lukas; Fischer-Kumbruch, Moritz; Trübenbach, Dominik; Fielbrand, Rieke; Schenk, Isabel; Diegmann, Oliver; Krauß, Terence; Scheinichen, Dirk; Schultz, Barbara
Abstract : Abstract: Postoperative delirium (PODE) can be associated with severe clinical complications; therefore, preventive measures are important. The objective of this trial was to elucidate whether haemodynamic or electroencephalographic (EEG) monitoring parameters during general anaesthesia or sevoflurane dosage correlate with the incidence of PODE. In addition, sevoflurane dosages and EEG stages during the steady state of anaesthesia were analyzed in patients of different ages. Eighty adult patients undergoing elective abdominal surgery received anaesthesia with sevoflurane and sufentanil according to the clinical routine. Anaesthesiologists were blinded to the EEG. Haemodynamic parameters, EEG parameters, sevoflurane dosage, and occurrence of PODE were analyzed. Thirteen patients (4 out of 33 women, 9 out of 47 men) developed PODE. Patients with PODE had a greater mean arterial pressure (MAP) variance (267.26 (139.40) vs 192.56 (99.64) mmHg 2, P = .04), had a longer duration of EEG burst suppression or suppression (27.09 (45.32) vs 5.23 (10.80) minutes, P = .03), and received higher minimum alveolar sevoflurane concentrations (MAC) (1.22 (0.22) vs 1.09 (0.17), P = .03) than patients without PODE. MAC values were associated with wide ranges of EEG index values representing different levels of hypnosis. The results suggest that, in order to prevent PODE, a great variance of MAP, higher doses of sevoflurane, and deep levels of anaesthesia should be avoided. Titrating sevoflurane according to end-tidal gas monitoring and vital signs can lead to unnecessarily deep or light hypnosis. Intraoperative EEG monitoring may help to prevent PODE.